The reliability and validity of a Chinese version of the Beach Center Family Quality of Life Scale in Mainland China for families of children with autism - Lu Liu; Lang-Fang Xie; Yi-Pei Xing; Yu Wang; Yue Ji; Miao-Ying Chen; Shuo Zhao; Fang Wang; Hai Li (BMC Pediatrics)
Abstract Purpose The objective of this study was to translate the Family Quality of Life (FQOL) Scale into simplified Chinese and assess its reliability and validity in mainland China for families of children with autism. Methods The FQOL Scale was professionally translated from English into simplified Chinese using a forward-backward process. We conducted a survey in which families with autistic kids were asked to participate, it comprised of a general condition questionnaire and the FQOL Scale translated to Chinese. A total of 402 families took part in the study, out of which 333 data sets were complete and available for analysis. The FQOL Scale model was subject to exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to probe its scale dimensional design and structure, as well as its adaptability to autistic children and their families using SPSS AMOS 24.0. The internal consistency and reliability was examined using Cronbach’s α (SPSS 22.0). And stepwise regression analysis was conducted to predict parents’ attitudes towards prognosis based on the five dimensions of the modified Chinese version of the FQOL Scale (SPSS 22.0). Results The data analysis yielded a revised Chinese version of the FQOL Scale. The analysis revealed that the overall reliability coefficient of the scale, as indicated by Cronbach’s α, was 0.918. The results of the CFA provided support for the best fit of a five-factor model (χ2 = 285.237, CFI = 0.930, TLI = 0.916, SRMR = 0.061, RMSEA = 0.062). The predictive equation for parents’ attitudes towards prognosis based on the five-dimensional model of the modified Chinese version of the FQOL Scale was as follows: Parent prognostic attitude = -0.863 + 0.456* Parenting + 0.2* Physical/Material Well-being. Conclusion The modified Chinese version of the FQOL Scale is suitable in mainland China for families of children with autism and has good reliability and model fit. The two dimensions of Parenting and Physical/Material Well-being can significantly predict parents’ prognostic attitude, indicating that the better the status of Parenting and Physical/Material Well-being, the better the parents’ prognosis attitude.